Dietary calcium deficiency suppresses follicle selection in laying ducks through mechanism involving cyclic adenosine monophosphate-mediated signaling pathway. (5th October 2020) - Chen, W.; Xia, W. G.; Ruan, D.; Wang, S.; Abouelezz, K. F. M.; Wang, S. L.; Zhang, Y. N.; Zheng, C. T.
Abstract : Ovarian follicle selection is a natural biological process in the pre-ovulatory hierarchy in birds that drives growing follicles to be selected within the ovulatory cycle. Follicle selection in birds is strictly regulated, involving signaling pathways mediated by dietary nutrients, gonadotrophic hormones and paracrine factors. This study aimed to test the hypothesis that dietary Ca may participate in regulating follicle selection in laying ducks through activating the signaling pathway of cyclic adenosine monophosphate (cAMP )/protein kinase A (PKA )/extracellular signal-regulated kinase (ERK ), possibly mediated by gonadotrophic hormones. Female ducks at 22 weeks of age were initially fed one of two Ca-deficient diets (containing 1.8% or 0.38% Ca) or a Ca-adequate control diet (containing 3.6% Ca) for 67 days (depletion period), then all birds were fed the Ca-adequate diet for an additional 67 days (repletion period). Compared with the Ca-adequate control, ducks fed 0.38% Ca during the depletion period had significantly decreased ( P < 0.05) numbers of hierarchical follicles and total ovarian weight, which were accompanied by reduced egg production. Plasma concentration of FSH was decreased by the diet containing 1.8% Ca but not by that containing 0.38%. The ovarian content of cAMP was increased with the two Ca-deficient diets, and phosphorylation of PKA and ERK1/2 was increased with 0.38% dietary Ca. Transcripts of ovarian estradiol receptor 2 and luteinizing hormone receptor ( LHR ) were reduced in the ducks fed the two Ca-deficient diets ( P < 0.05), while those of the ovarian follicle stimulating hormone receptor ( FSHR ) were decreased in the ducks fed 0.38% Ca. The transcript abundance of ovary gap junction proteins, A1 and A4, was reduced with the Ca-deficient diets ( P < 0.05). The down-regulation of gene expression of gap junction proteins and hormone receptors, the increased cAMP content and the suppressed hierarchical follicle numbers were reversed by repletion of dietary Ca. These results indicate that dietary Ca deficiency negatively affects follicle selection of laying ducks, independent of FSH, but probably by activating cAMP/PKA/ERK1/2 signaling pathway.